The Influence of Learning Interest on Understanding of Mathematical Concepts in Class XI PH 1 Students at SMKN 6 - Ginne, Yusri; Kariman, Delsi; Yusri, Radhya (AlphaMath : Journal of Mathematics Education, 2024)
This study aims to determine the effect of learning interest on understanding of mathematical concepts in class XI PH 1 students at SMKN 6 Padang. Research subjects were selected using purposive sampling with a total of 26 students. The approach used in this research is quantitative and analyzed by simple linear regression using the R program. The technique of collecting data by providing non-test instruments in the form of questionnaires on students' learning interests and test instruments about number patterns to measure understanding of mathematical concepts. Hypothesis testing is done by simple regression, by first looking at the pattern of relationships between variables and determining the correlation coefficient. The result showed that there is no significant effect of learning interest on understanding mathematical concepts with regression equation Y=35.3555+0.3379X. So, it can be concluded that learning interest has no significant effect on students' ability to understand mathematical concepts.